Just how competitive are we? Managing organizational culture in a Canadian university athletics department - Woolf, Jules; Green, B. Christine; Dixon, Jess C.; Hill, Patrick J. (London : Human Kinetics, Inc., 2019)
Christiaan Jacobs is the new Dean of Student Affairs at the University of South Central Ontario, which puts him in charge of the Department of Athletics and Recreation. Jacobs has learned that the hypercompetitive environment established by the athletic director, Nathan Scott, has been causing friction in many areas of the department, potentially resulting in the resignation of several long-term employees. As part of an organizational audit, he interviewed many employees and had them complete the Competing Values Framework questionnaire, the results of which were troubling. How should Jacobs lead this department forward and can he count on Scott to be supportive of the direction that he wants it to go? The purpose of this case is to introduce students to the importance of organizational culture and challenges to organizational change. Students will learn about the Competing Values Framework, change management, and have the opportunity to analyze qualitative and quantitative data in formulating responses to the case-guiding questions. This decision-focused case is suitable for use with upper division undergraduate and graduate sport management students in courses such as Organizational Behavior, Strategic Management, Collegiate Athletics Administration, and Critical Issues in Sport.
Originally Published InWoolf, J., Green, B. C., Dixon, J. C., & Hill, P. J. (2019). Just How Competitive Are We? Managing Organizational Culture in a Canadian University Athletics Department. Case Studies in Sport Management, 8(1), S21-S27.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporate culture -- Case studies; Organizational behavior -- Case studies